Innovation or Tradition? Succession to the Kingship in Temenid Macedonia - Psoma, Selene E. (Tekmeria, 2013)
<span style="font-size: 10.0pt; font-family: Gentium; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: Arial; color: black; letter-spacing: -.1pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">This article attempts to show that the free designation of the successor to the throne by Ptolemy I and Seleukos I, and the association in power of the successor during the last years of the king’s reign, was not an innovation of the age of the Diadochi but an old Macedonian practice. Using IG II/III2 102, the treaty between Athens, Amyntas II and his son Alexander as a starting point, this work collects all the evidence for the designation of the succesor to the throne in the Temenid Kingdom, discusses previous theories about succession, and argues that the successor was designated by the king himself, who appears to have had full jurisdiction to decide on the matter freely, unimpeded by custom or law.